10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Environmental enrichment can promote natural behaviours and improve welfare in captive birds, but its effectiveness may depend on species-specific ecological and behavioural adaptations, particularly feeding ecology. OBJECTIVES: This study aims to evaluate the effectiveness of naturalistic nectar bucket feeding enrichment devices in two parrot species with contrasting feeding strategies: rainbow lorikeets (Trichoglossus moluccanus), which are primarily nectivorous, and regent parrots (Polytelis anthopeplus), which are primarily granivorous. METHODS: Forty-five rainbow lorikeets and 11 regent parrots were observed under two nectar-feeding conditions: bowl only, where nectar was provided in bowls alone, and bucket + bowl, where nectar was provided simultaneously in bowls and nectar buckets. Behaviour was recorded using instantaneous scan sampling for three 30-min observation periods (before, during, and after presentation of the experimental condition) and classified into four categories: ground, aerial, bowl, or bucket activity. RESULTS: Rainbow lorikeets spent significantly more time engaged in aerial activity during both feeding conditions than during the after period. They also interacted more frequently with the nectar bucket and reduced their use of bowls when buckets were available. In contrast, regent parrots showed no significant changes in general behaviour or in their use of bowls or buckets across observation periods or feeding conditions. CONCLUSIONS: The nectar bucket feeding devices effectively promoted species-typical foraging behaviour in rainbow lorikeets but had little effect on regent parrots, reflecting differences in feeding ecology. These findings highlight the importance of designing enrichment that is tailored to species-specific ecological and behavioural needs and evaluating enrichment based on both its biological relevance and its overall effectiveness.